Pelatihan Mendeley Bagi Mahasiswa Magister Manajemen Universitas Gorontalo - Wahyudin Hasan; Ayub Usman Rasid; Deby Rita Karundeng (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
The use of reference manager software in writing a scientific paper is an obligation for students of the Postgraduate Program at the University of Gorontalo. Unfortunately, there are still many masters of management students who don't know how to use the application at all. The purpose of this activity is to train students to get used to using the Mendeley application in writing a scientific paper. The method used is by conducting a direct introduction and training on how to use Mendeley. The results of this activity are (1) Students get new information and knowledge about reference manager software and citation techniques. (2) Students can apply the use of Mendeley software when compiling scientific work.